Farmers’ Education and Farm Productivity in Bangladesh - Haq, Abu Zafar Mahmudul (Richtmann Publishing, 2012)
The impact of farmers’ education is examined with a view to evaluate the actual situation of farmers’education in Bangladesh. The sample of the study consists of one thousand farmers. Multiple regressionmodel was used. The result presented in this paper show that the returns to education from primary schoolis positive and statistically significant in Bangladesh. The benefit of college education and above degrees tothe sample farms is not found in its effect on rice productivity. Some determinants of primary school,college and above degrees are also examined.